Analysis of spinal EMG signal when swinging an object - Bahar, Mohd Bazli; Too, Jing Wei; Miskon, Muhammad Fahmi; Mohd Sobran, Nur Maisarah; Mohd Shaari Azyze, Nur Latif Azyze (Research India Publications, 2017)
Electromyography (EMG) is bio signal record the electricity generated by muscle, but the signal often influenced by the unwanted noise. In this paper, MVC normalization method is applied to determine the spinal EMG signal on lumbar multifidus muscle when swinging an object. In order to analyse the identical and recognition of spinal EMG signal, three statistical analyses are done. There is one-way ANOVA analysis, RMS analysis and boxplot analysis. The result of MVC test shows that a higher percentage of MVC resulted in higher normalized amplitude. One-way ANOVA analysis shows that the means value among all 15 subjects are different in 100% MVC test. In addition, RMS analysis indicates that the muscle activity is increased when the muscle contraction is increased. In boxplot analysis shows that the increment of percentage MVC resulted in greater median, normalized amplitude and interquartile range. Besides, this paper presents a further investigation on determining the average median and interquartile range different from 0% until 100% MVC test by applied 8